Relationship of Candida albicans Urinary Colony Count and Glucosuria in Elderly Diabetics: Hubungan Jumlah Koloni Candida albicans Urin dan Glukosuria pada Lansia Penderita Diabetes - Nadyah Saffana Fadhilla; Muhammad Taufiq Qurrohman (Universitas Muhammadiyah Sidoarjo, 2025)
Diabetes mellitus is a global health problem with a high prevalence in the elderly and is associated with an increased risk of opportunistic infections. One of the common accompanying conditions is glucosuria, caused by elevated urinary glucose excretion, which may promote the growth of Candida albicans. This study aimed to examine the relationship between urinary glucosuria and the number of Candida albicans colonies in elderly patients with diabetes mellitus at Griya Sehat Colomadu Clinic. Urine samples were tested for glucosuria using the dipstick method, while urine cultures were performed on CHROMagar Candida medium to identify and quantify Candida albicans colonies. Data were analyzed using the Spearman correlation test. Most respondents were negative for glucosuria (57,14%), while the remainder were positive with varying degrees. The colony counts of Candida albicansranged from 0 to 319.000 CFU/mL, with median counts increasing alongside the degree of glucosuria. Statistical analysis revealed a strong and significant positive correlation between glucosuria and Candida albicans colony counts (r = 0,700; p < 0.01). Higher levels of glucosuria are associated with increased Candida albicans colony counts in the urine of elderly patients with diabetes mellitus. These findings highlight the importance of controlling blood glucose levels and routinely monitoring urine cultures to prevent opportunistic fungal infections in elderly diabetic patients.